Response of Sugarcane Varieties L. Saccharum Officinarum to Foliar Feeding with Nano-Fertilizers Under Drip Irrigation Technology - Amjad Shaker Hamoud Al-Bawi; Raghda Safaa Alddin; Shuaa Majid Al-Zubaidi; Omar Mohammed Shadhan (Academia Open, 2025)
General Background: Sugarcane is a major tropical crop whose productivity depends on efficient nutrient management and irrigation systems. Specific Background: Recent advances in nanotechnology have introduced nano-fertilizers capable of enhancing nutrient uptake and improving physiological performance, yet their crop-specific efficacy under drip irrigation remains insufficiently characterized. Knowledge Gap: Empirical evidence on how distinct sugarcane varieties respond to varying nano-fertilizer concentrations in field conditions—particularly regarding vegetative growth, yield components, and sucrose accumulation—is still limited. Aims: This study evaluated the growth, physiological traits, and yield of four American sugarcane cultivars (CP72-2086, CP89-2143, CP81-325, LO3-371) subjected to three nano-fertilizer concentrations (1, 2, 3 L ha⁻¹) under drip irrigation. Results: The 3 L ha⁻¹ treatment consistently improved stem height, diameter, leaf area, and stem yield (229.67 t ha⁻¹), while cultivars CP89-2143 and CP81-325 showed the highest sucrose content (up to 16.20%). LO3-371 exhibited the greatest increase in extractable stems and dry biomass. Novelty: This study provides the first integrated comparison of nano-fertilizer dose–response patterns across multiple sugarcane varieties under drip irrigation in arid-field conditions. Implications: Findings highlight the potential of nano-fertilizers—particularly at 3 L ha⁻¹—to enhance growth efficiency and sugar yield, supporting more sustainable and productive sugarcane management strategies.Highlight : Nano-fertiliser 3 L ha⁻¹ consistently improves stem growth and leaf performance. Varieties CP81-325, CP89-2143, and LO3-371 show stronger vegetative responses. Sucrose and sugar yield increase under optimized nano-fertiliser levels with drip irrigation. Keywords : Stem Height, Sugar Yield, Nano-fertiliser, Sugarcane Varieties, Drip Irrigation